ARL8B regulates lysosomal function and predicts poor prognosis in hepatocellular carcinoma - Liyan Wu; Zelin Weng; Xia Yang; Yuhua Huang; Yansong Lin; Shuo Li; Lingyi Fu; Jingping Yun (Scientific Reports)
Abstract Adenosine 5′-diphosphate ribosylation factor–like 8B (ARL8B), a small GTPase, is involved in lysosome motility. Our study investigates the role of ARL8B in hepatocellular carcinoma (HCC) using in vitro and in vivo experiments, bioinformatics, and clinical data. We found that ARL8B expression is abnormally elevated in HCC and correlates with poor prognosis. ARL8B knockdown triggered lysosomal dysfunction—manifesting as abnormal morphology, decreased pH, reduced hydrolase activity, and impaired autophagic degradation—which subsequently led to cell cycle arrest and reduced cell viability. Additionally, tumors with high ARL8B expression (ARL8Bhigh) exhibited notable differences in tumor microenvironment composition compared to those with low ARL8B expression (ARL8Blow). ARL8Bhigh HCCs had significantly increased infiltration of NFKBIZ+/HIF1A+ and VEGFA+/SPP1+ neutrophils. EcoTyper analysis indicated that ARL8Bhigh HCCs had a lower proportion of carcinoma ecotype 6, a cellular ecosystem common in normal tissues but rare in tumors. Bioinformatics and real-world analysis showed a positive correlation between ARL8B and PD-L1 expression. Patients with high ARL8B expression exhibited increased sensitivity to sorafenib and immune checkpoint blockade therapy. In conclusion, our findings identify ARL8B as a key lysosomal regulator associated with tumor microenvironment composition in HCC, suggesting its potential as both a therapeutic target and a biomarker for predicting treatment response.